Lacan e o estruturalismo - Felizola, Maria Cristina Merlin (Universidade Federal de São Carlos, 2000)
The present work has arisen of the need to understand the Lacan statement "the unconscious is structuralized as language". With this affirmation Lacan has pointed to two important directions: His incursion to the structuralism movement and the adoption of the Linguistics as reference. First we feel the necessity to know the structuralism movement and its bigger contributors. The structuralists have had much concern in searching a model which could explain the biggest possible number of aspects of a phenomenon, in a simpler and economic. In relation to the Linguistics the contribution came from the Fonology, this served as model for considering the terms in its internal relations, for introducing the structure notion and also searching the general laws construction. The formalization degrees that the Linguistics reach was such that it started to serve as influence for others disciplines of human being sciences, in their intention to ascend to the category of rigorous sciences. The structuralism brought a new method to approach the societies and the man. The unconscious, the primitive society and everything that had been depressed in the occidental History has found a place in the movement that searched the grammar of the human being thought.
Keywords: Lacan, Jacques, 1901-1981; Estruturalismo; Psicanálise; Linguagem; CIENCIAS HUMANAS::FILOSOFIA